Використання золи теплоелектростанцій у виробництві бетону - Клапченко В. І., Краснянський Г. Ю., Азнаурян І. О., Кузнецова І. О. (Енергоефективність в будівництві та архітектурі. – 2018. – №10. – С. 47-53., 2018)
In order to reduce the cost and energy intensity of concrete, reducing the negative impact on the environment during its production, industrial waste is widely used, in particular, the ash of removal of heat and power plants. The results of studies of equilibrium water-holding and mass-transfer properties of a soluble part of concrete with additives of ashes of thermal power stations are presented in order to obtain additional information on the mechanism of interaction between particles of ash and cement and its relationship with the strength indicators of the cement-ash materials. The methods of isotherms of desorption and capillary impregnation are measured equilibrium moisture content at different humidity of air, differential gradient distribution curves according to radii, maximum moisture content, capillary-toporosity and coefficient of mass transfer of the rising part of concrete with additives of ashes of Krivorizhsky and Ladyzhinskaya TPPs. The results were obtained for specimens that were subjected to thermovalysis and for specimens after 28 days of prime hardening. In the approximation of the monodisperic globular structure of the investigated materials, the effective radius of pores involved in the mass transfer and the coefficient of filtration are calculated. The compressive strength of these materials is also measured. On the basis of the conducted researches, the nature of the influence on the change in the strength parameters of these materials of such factors as granulometric, chemical, phase composition of ash, water-cement ratio, and curing mode is established. It is shown that in order to adequately integrate the obtained results it is necessary to simultaneously take into account such factors as the content of ash in the mixture, the water-cement ratio, porosity, effective pore radius, pore size distribution. It is shown that there is a gap-free correlation between the strength of materials compression and the coefficient of filtration. There were proposed optimal concrete compositions with ashes additions.
Keywords: Бетон, зола теплоелектростанцій, водоутримуючі та масопереносні властивості, міцність.; 666.97